Remediation Potential of Borehole Thermal Energy Storage for Chlorinated Hydrocarbon Plumes: Numerical Modeling in a Variably-Saturated Aquifer - Meng, Boyan; Yang, Yan; Huang, Yonghui; Kolditz, Olaf; Shao, Haibing (Frontiers in Earth Science, 2021)
Underground thermal energy storage is an efficient technique to boost the share of renewable energies. However, despite being well-established, their environmental impacts such as the interaction with hydrocarbon contaminants is not intensively investigated. This study uses OpenGeoSys software to simulate the heat and mass transport of a borehole thermal energy storage (BTES) system in a shallow unconfined aquifer. A high-temperature (70 °C) heat storage scenario was considered which imposes long-term thermal impact on the subsurface. Moreover, the effect of temperature-dependent flow and mass transport in a two-phase system is examined for the contaminant trichloroethylene (TCE). In particular, as subsurface temperatures are raised due to BTES operation, volatilization will increase and redistribute the TCE in liquid and gas phases. These changes are inspected for different scenarios in a contaminant transport context. The results demonstrated the promising potential of BTES in facilitating the natural attenuation of hydrocarbon contaminants, particularly when buoyant flow is induced to accelerate TCE volatilization. For instance, over 70% of TCE mass was removed from a discontinuous contaminant plume after five years operation of a small BTES installation. The findings of this study are insightful for an increased application of subsurface heat storage facilities, especially in contaminated urban areas.